2007
DOI: 10.1007/s00595-007-3541-5
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Sewn Cervical Anastomosis Versus Stapled Intrathoracic Anastomosis After Esophagectomy for Middle or Lower Thoracic Esophageal Cancer: A Prospective Randomized Controlled Study

Abstract: The two methods of anastomosis yielded similar anastomotic outcomes. Although the incidence of recurrent laryngeal nerve injury was higher after CHS, and proximal esophageal resection was longer, this had little impact on postoperative symptoms and long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
97
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 19 publications
4
97
1
5
Order By: Relevance
“…Our results demonstrated that the total complication rate in the new manual technique group was 7.4% and the anastomotic complication rate was zero, which was lower than that recorded in the traditional technique group and previous studies (4)(5)(6)(7)(8).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Our results demonstrated that the total complication rate in the new manual technique group was 7.4% and the anastomotic complication rate was zero, which was lower than that recorded in the traditional technique group and previous studies (4)(5)(6)(7)(8).…”
Section: Discussioncontrasting
confidence: 60%
“…The main anastomotic complications include leakage, stricture and infection. It was reported that, in esophagogastric anastomosis, the incidence rate of leakage and stricture was 0-21.9 and 0-25.8%, respectively, with manual suturing and 0-19.5 and 0-32.8%, respectively, with surgical stapling (4)(5)(6)(7)(8). Furthermore, the incidence of leakage was reported to be 2.6-17% in low anterior resection for rectal cancer with the double-stapling technique (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, hypoalbuminemia, neoplastic permeation of the anastomotic cut margin, and cervical anastomosis were associated with a higher incidence of anastomotic leakage (27). other possible risk factors include weight loss, history of taking steroids, neoadjuvant chemoradiotherapy, long operation time, multiple blood transfusions and technical factors (26)(27)(28)(29). In this study we showed that addition of splenectomy is associated with four time increase in the rate of anastomotic leakage.…”
Section: Discussionmentioning
confidence: 49%
“…Handling the stomach gently and preserving as many collaterals as possible is the key. We have to emphasize that we did all our cervical anastomose with hand-sewn technique, and the leakage rate was even lower than the reported rate by stapler method (16,17).…”
Section: Discussionmentioning
confidence: 99%